The Enforcement of Marriage Law (No 16 of 2019) Through The Ambassadors of Child Marriage Prevention in Tembarak District, Temanggung Regency - Hidayatun Ulfa; Sholeh Kurniandini; Azim Miftachul Ihsan; Husna Nashihin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The enforcement efforts of Law Number 16 of 2019 on marriage performed in Temanggung are designed to minimize the divorce rate in Temanggung through the empowerment of Sakinah family ambassadors through pre-marriage education to actualize family resilience. The practical benefit of this study is that it can give insight to the ambassadors about the age limit of marriage and the consequences of early marriage. The ambassadors are meant to use the insight to take action against early marriage so that the number of cases of early marriage in the Tembarak district continuously decreases or even reaches zero. This study employs a descriptive qualitative research approach to explain the enforcement efforts of Law Number 16 of 2019 on marriage in Temanggung. The implementation of Marriage Law Number 16 of 2019 is carried out through a number of Focus Group Discussions (FGD): youth guidance, and ambassadors coaching to prevent early marriage; mentoring; monitoring and evaluation; and outcome exposure. This research intends to lower the number of early marriages among Tembarak District school-age students (Junior and High school students: SMP/MTs and SMS/MA/SMK). The implementation of Law Number 16 of 2019 on marriage is carried out through intense socialization in school assemblies in Temanggung